2013
DOI: 10.4172/2332-0761.1000121
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Antecedents of Political Engagement Behavior among Young Adult College Students

Abstract: Aim: This study assesses the impact of political social motivation, trust in government, political efficacy, and personal motivation on political engagement behavior among young adult college students. Study design: Quasi-experimental One-shot Case Study Design. Methodology: Survey data of indicators of the five latent constructs was collected from college students. Exploratory principal component factor analysis and Cronbach's alpha test were performed to identify the factorial structure of the each of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Specifically, studies conducted in the US [7] and Sweden [8] have shown that social media has significantly influenced political participation among youths. However, some scholars have noted that there is decrease or non-participation of youths in politics whether online or offline [9]. Accordingly, researches in this area have presented mixed results.…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, studies conducted in the US [7] and Sweden [8] have shown that social media has significantly influenced political participation among youths. However, some scholars have noted that there is decrease or non-participation of youths in politics whether online or offline [9]. Accordingly, researches in this area have presented mixed results.…”
Section: Introductionmentioning
confidence: 95%
“…However, other scholars have argued that rather than the increase in youth online political participation noticed by some, there is actually a decrease or even in some cases, total nonparticipation of youths in politics (Seongyi & Woo-Young, 2011;Iyengar & Jackman, 2004;Mongkuo, Lyon, Hogan, & Delore, 2014;Wells & Dudash, 2007; 2011) yet, not much studies are being carried out in this area especially in relation to online political participation. Nevertheless, scholars (Chun, 2012;Dalton, 2008;Putnam, 2000) have observed that the responsibility for non-participation should not be placed squarely on the youths, but rather on the reason why they don't participate in conventional politics.…”
Section: Introductionmentioning
confidence: 99%